Fabrication and antimicrobial analysis of composite biodegradable film from pumpkin starch - Ahmad Bazli, Bustary (2010)
The purpose of the research is to fabricate difference types of composite biodegradable films from pumpkin starch, to analyze antimicrobial activities of chitosan-incorporated pumpkin starch films and to characterize the biodegradable film (pumpkin starch) in term of physical properties. In this study, the pumpkin starch is used as a raw material because of its high composition of starch. The process involve for this experiment are preparation of pumpkin flour and then the starch is isolated from the pumpkin flour by mixing with the water and settling it over night without shaking to recover the sediment as a pumpkin starch. The next process is to prepare the film by adding the polyethylene glycol (PEG) as plasticizers at a concentration of 3% and the chitosan was added in a different concentration (1.5g, 2.0g, 2.5g) as preparation of microbial film and mixing all of component. After being heated the solution, the warm mixture was casted on framed glass plates, and then dried at a room temperature for 8 hours. Then, the sample is characterized after the film is produced. The analysis shows that the sample with high concentration of chitosan has lower water solubility. The percentage of water solubility in each sample 1.5g, 2.Og and 2.5 g chitosan is 69.7%, 65.2% and 52.3% respectively. The Fourier transforms infrared spectroscopy (FTIR) result show that the similar pattern of peak at wavenumbers range 1500 cm -1600 cm-1 with addition of chitosan the peak become narrower and weaker. Thus, the addition of chitosan can disturb the crystalline of the starch which is the main factor to determine the characteristic of biodegradable film. The antimicrobial analysis shows that the Escherichia coil and Bacillus subtilis cannot growth well at the film surface. The microorganism colonies are smaller in the film with high concentration of chitosan. The scanning electron microscope (SEM) show that the characteristic features with high concentration of chitosan has a smooth surface compare to the other sample because of the high bonding between the molecules in the sample.